Analyzing Pricing Strategy in Competitive E-Commerce Ecosystem Like Tokopedia and Shopee - Riska Anggraeni; Nur Saebah; Dina Nurul Fathiya (Journal of Strategic Marketing and Applied Economics, 2025)
The rapid growth of e- commerce in Indonesia has created a highly competitive business environment, with Tokopedia and Shopee becoming the two dominant platforms. Price competition has become a key strategy to attract price- and promotion-sensitive digital consumers. However, the pricing dynamics between these two platforms have not been comprehensively studied, particularly in the context of long-term strategies and their impact on customer loyalty. This study aims to analyze the pricing strategies implemented by Tokopedia and Shopee in their efforts to maintain and increase their market share. The research method used was a descriptive qualitative approach with a case study technique. Data were collected through in-depth interviews with active business owners on both platforms, analysis of price promotion content from 2023 to 2024, and observation of secondary data from e- commerce industry reports . The results show that both platforms rely on deep discount strategies, shipping subsidies, and automatic price adjustment algorithms to maintain competitiveness. Shopee tends to be more aggressive in loyalty programs and price campaigns, while Tokopedia places greater emphasis on financial services integration as an added value. Dynamic pricing strategies have proven effective in increasing short-term transactions, but present sustainability challenges for small businesses. This research contributes to the understanding of digital marketing strategies and offers practical implications for MSMEs and policy makers in designing fair e- commerce regulations.